The International and Political Journal: The energy variable in the Chinese Middle Eastern strategy after 2003 :Iraq as an example - Aziz, Assistant lecturer Dr. Abbas Hashem; Radi, Adel Mahwadar (The International and Political Journal, 2024)
China is seeking to secure energy sources to support its rapid economic growth. Since the invasion of Iraq in 2003, China has intensified its efforts to achieve this goal in the Arab region, adopting a strategy based on a soft power policy, drawing on the ancient and modern historical link of the Silk Road. This strategy seeks to enhance communication and cooperation with Arab countries. Chinese relations with Arab countries have witnessed significant development since 2003. China established the Arab-Chinese Cooperation Forum in 2004, and issued its first Arab policy paper in 2016, which included three main pillars of cooperation between China and Arab countries, namely, energy, followed by the second pillar. The essential basis for cooperation with Arab countries, as they seek to secure oil and gas supplies from the region. With its focus on cooperation in the field of infrastructure as a second pillar, including transportation, energy and communications projects, as well as the third pillar, which is its pursuit of cooperation in the field of technology, including nuclear energy, satellites and new energy sources. As a result of these efforts, China was able to enhance its influence in the oil and gas sector in the Arab region. In Iraq, Chinese companies obtained contracts to exploit important oil fields, such as Al-Ahdab, Aqaba, Nasiriyah, and Al-Masila. China has also become the largest importer of Iraqi oil, and Chinese companies have also participated in infrastructure, energy and communications reconstruction projects in Iraq, which enhances economic cooperation and sustainable development in the region. In this way, China is demonstrating its comprehensive and integrated strategy in the region, focusing on economic and energy cooperation to ensure the sustainability of its economic growth.